Globalisation and regional variety: problems of theorisation - Schwinn, Thomas (Comparative education, 2012)
Increasing globalisation is concomitant with a growing lack of uniformity in the world. Hardly any satisfactory concepts are available which grasp both of these tendencies within the scope of a single model. While processes of becoming globally alike are central to world system theories, comparative research into institutions has identified a persistent variety of patterns of order that are not giving way to global convergence. Just as the historical breakthrough to modernity was of central interest to the classical authors of sociology, the global spread of modernity also requires appropriate theory-building. Current globalisation theories, however, remain strongly shaped by the models put forward by the classics, who emphasised modernity's universalising potentials. Accordingly, local and regional variations are underexposed in conceptual terms. This is demonstrated with reference to various globalisation theorems, and alternative theories are proposed with detailed analyses of the relationship between structural and cultural factors. The article presented here proposes that the ‘world system’ concept should be replaced with an ‘actor/structure’ model in which the global and the local are not understood as completely different fields of phenomena but are instead elucidated in terms of their relations of reciprocal constitution.
Gesehen am 06.12.2018